2,15-Dioxa-7,18,19,20,23-pentaazaheptacyclo[21.6.1.1(17,20).0(1,8).0(3,7).0(9,14).0(24,29)]hentriaconta-9,11,13,17(31),18,24,26,28-octaen-30-one - Subhashree, Govindarajulu Rangabashyam (International Union of Crystallography, 2013)
In the title compound, C(24)H(23)N(5)O(3), the oxindole ring system is nearly planar, with a dihedral angle between the two fused rings of 3.3 (1)°. In the fused pyrrolo–oxazole ring system, the oxazole and pyrrolidine rings adopt envelope conformations with the spiro C atom and one of the methylene C atoms, respectively, as the flap atoms. In the crystal, molecules are linked into a helical chain along the b axis via C—H⋯O interactions generating R (2) (1)(7) and R (2) (2)(8) ring motifs.